2013
DOI: 10.1074/jbc.m112.413856
|View full text |Cite
|
Sign up to set email alerts
|

Myotubularin-related Protein 4 (MTMR4) Attenuates BMP/Dpp Signaling by Dephosphorylation of Smad Proteins

Abstract: Background:The intensity and duration of phosphorylation levels of R-Smads are required for precise control of BMP signaling. Results: MTMR4 associated with and dephosphorylated the activated R-Smads in cytoplasm. Conclusion: MTMR4 attenuates BMP signaling via its DUSP activity. Significance: This study describes a novel role of MTMR4 as a negative modulator essentially involved in homeostatic BMP signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…Conversely, dephosphorylation of Smad1/5/8 represents a critical event in terminating BMP signaling. Phosphatases that have been reported to dephosphorylate Smad1/5/8 include the panSmad phosphatase PPM1A (19,20), SCP1/2/3 (22, 24), PDPs (21), and MTMR4 (23). In various cell types, we found that PPM1A, but not the others, plays a major role of pan-Smad dephosphorylation (19).…”
Section: Depletion Of Ppm1a Does Not Fully Sustain Smad1mentioning
confidence: 67%
See 1 more Smart Citation
“…Conversely, dephosphorylation of Smad1/5/8 represents a critical event in terminating BMP signaling. Phosphatases that have been reported to dephosphorylate Smad1/5/8 include the panSmad phosphatase PPM1A (19,20), SCP1/2/3 (22, 24), PDPs (21), and MTMR4 (23). In various cell types, we found that PPM1A, but not the others, plays a major role of pan-Smad dephosphorylation (19).…”
Section: Depletion Of Ppm1a Does Not Fully Sustain Smad1mentioning
confidence: 67%
“…Several phosphatases were identified as the phosphatases toward the dephosphorylation of R-Smads, including PPM1A as a pan-Smad phosphatase (19,20). Smad1 is also reported to be dephosphorylated by pyruvate dehydrogenase phosphatase (PDP) (21), small C-terminal phosphatases (SCP1/2/3) (22), and endosomal phosphatase MTMR4 (23). Meanwhile, SCP1/2/3 can target the linker region of R-Smads (22,24,25) In this study, we showed that knockdown of PPM1A failed to completely restore the level of phospho-Smad1 (P-Smad1), suggesting the existence of other phosphatases toward P-Smad1.…”
mentioning
confidence: 99%
“…Also, MTMR4 colocalizes with the exocyst subunit Sec15 and affects localization of VAMP3-containing endosomes (Lorenzo, Urbe et al 2006;Naughtin, Sheffield et al 2010). Additionally to PI(3)P, MTMR4 dephosphorylates RSmads at early endosomes and thereby negatively regulates TGF-ÎČ (transforming growth factor) (Yu, Pan et al 2010) and BMP (bone morphogenetic protein) signaling pathways (Yu, He et al 2013). …”
Section: Other Myotubularin Family Members Contribute To Endosomal Pimentioning
confidence: 99%
“…15 Pyruvate dehydrogenase phosphatase (PDP), which is localized in mitochondria, was the first phosphatase to be reported as a SMAD1 tail phosphatase. 16 In addition, SCPs were proposed to be a SMAD1 tail phosphatase through depletion and overexpression studies.…”
Section: +mentioning
confidence: 99%